2021
DOI: 10.1111/1755-0998.13523
|View full text |Cite
|
Sign up to set email alerts
|

Taxon‐specific or universal? Using target capture to study the evolutionary history of rapid radiations

Abstract: Target capture has emerged as an important tool for phylogenetics and population genetics in nonmodel taxa. Whereas developing taxon‐specific capture probes requires sustained efforts, available universal kits may have a lower power to reconstruct relationships at shallow phylogenetic scales and within rapidly radiating clades. We present here a newly developed target capture set for Bromeliaceae, a large and ecologically diverse plant family with highly variable diversification rates. The set targets 1776 cod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 138 publications
3
37
0
Order By: Relevance
“…Our results are in general consistent with the phylogenetic relationships recovered by previous studies using plastid data ( Barfuss et al, 2016 ; Machado et al, 2020 ; Loiseau et al, 2021 ), albeit in discordance with the phylogenetic relationships retrieved by Loiseau et al (2021) based on nuclear data, where subtribe Cipuropsidinae (tribe Vrieseeae) is recovered as sister to tribe Tillandsieae (vs. sister to subtribe Vrieseinae), and Werauhia is retrieved as sister to the remaining genera of subtribe Cipuropsidinae (vs. sister to Lutheria ). Genus level phylogenetic relationships obtained by Yardeni et al (2022) from the analysis of their nuclear dataset are mostly in agreement with our results, except for the position of Racinaea which is recovered nested within Tillandsia by these authors. Despite the differences in taxon samplings across studies, the consistently retrieved strongly supported phylogenetic discordance between plastid and nuclear data sources suggest that evolutionary processes, such as hybridization or lineage sorting, could have shaped the evolution of the core Tillandsioideae.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are in general consistent with the phylogenetic relationships recovered by previous studies using plastid data ( Barfuss et al, 2016 ; Machado et al, 2020 ; Loiseau et al, 2021 ), albeit in discordance with the phylogenetic relationships retrieved by Loiseau et al (2021) based on nuclear data, where subtribe Cipuropsidinae (tribe Vrieseeae) is recovered as sister to tribe Tillandsieae (vs. sister to subtribe Vrieseinae), and Werauhia is retrieved as sister to the remaining genera of subtribe Cipuropsidinae (vs. sister to Lutheria ). Genus level phylogenetic relationships obtained by Yardeni et al (2022) from the analysis of their nuclear dataset are mostly in agreement with our results, except for the position of Racinaea which is recovered nested within Tillandsia by these authors. Despite the differences in taxon samplings across studies, the consistently retrieved strongly supported phylogenetic discordance between plastid and nuclear data sources suggest that evolutionary processes, such as hybridization or lineage sorting, could have shaped the evolution of the core Tillandsioideae.…”
Section: Discussionsupporting
confidence: 91%
“…Then, Loiseau et al (2021) expanded the plastid genomic dataset of Machado et al (2020) , by mining additional nuclear and mitochondrial loci for an increased taxon sampling. Lastly, Yardeni et al (2022) explored the utility of two nuclear target capture kits to resolve phylogenetic relationships in Bromeliaceae, including 56 species of the subfamily Tillandsioideae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, bioinformatic analyses took longer due to the iterative refinement, and only a portion of captured sequence data was ultimately used for phylogenomic or population genomic analyses in each focal group (see Tables S1–S3 ). Higher costs per used sequence could be compensated by enriching DNA of up to six individuals in a single hybridization reaction, a strategy that has been used successfully in other studies (e.g., de La Harpe et al, 2018 ; Yardeni et al, 2022 ). To further reduce costs, future target enrichment experiments in Dalbergia could be focused on genomic regions targeted by the 6190 sequences of the Dalbergia2396 probe set.…”
Section: Discussionmentioning
confidence: 99%
“…However, several comparisons revealed that microevolutionary relationships are often better resolved when targeting more loci using taxon‐specific probe sets (e.g., Shah et al, 2021 ; Siniscalchi et al, 2021 ; Ufimov et al, 2021 ). The development of taxon‐specific probe sets therefore remains valuable for detailed phylogenetic and population genetic analyses (Yardeni et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%